Does the Factors Affecting Gold Price Changed During Covid-19 Period in Malaysia? - Damien Iung Yau, Lee; Pei Ching, Chiam; Josephine Tan Hwang, Yau; Kit Yeng, Sin; Joanne Shaza, Janang (Human Resource Management Academic Research Society, 2021)
This paper examines whether Covid-19 pandemic has changed the main economy factors affecting gold prices, and the relationship between KLCI and gold price in Malaysia. Gold plays an important role in an economy during normal and uncertain market situations. This research involved 62 monthly data covering the period of January 2016 to February 2021. Unit root and diagnostic tests are conducted on the data to ensure the results are valid. There are six macroeconomic variables involved, five of them are the independent variables and the remaining one is dependent variable. Multiple regression time series analysis is use to analyse the data in the perspectives of full sample, pre- Covid-19 period and during Covid-19 period. The results of this study found that few main economy factors ceased to be significant, and there is change relationship direction between exchange rate and gold price during Covid-19 period. We discovered KLCI has an inverse relationship with gold price. Future research can consider extending our analysis to neighbouring countries.